PENGARUH ECONOMIC VALUE ADDED, DEGREE OF OPERATING LEVERAGE, DEGREE OF FINANCIAL LEVERAGE, DEGREE OF COMBINED LEVERAGE, RETURN ON EQUITY, DAN RETURN ON ASSETS TERHADAP RETURN SAHAM LQ 45 TAHUN 2005, 2006, 2007, DAN 2009. - Akromul Ibad, MM; paulus SE (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2011)
The purpose of this study isto examine the influence of the economic value added (EVA), degree of operating leverage (DOL), degree of financial leverage (DFL), degree of combined leverage (DCL), return on equity (ROE), and return on assets (ROA) toward the stock return included in LQ45 on the Indonesia Stock Exchange. Every company has a permanent burden in terms of both operational and financial leverages, so it has a risk due to fixed expenses. It is hypothetically predicted that the leverage and financial performance would affect the stock return. By implementing purposive sampling method, sample of this study consist of 18 listed companies for the period of 2005, 2006, 2007, and 2009. Data analysis of this study employs multiple linear regression and classic assumption test. This study concludes that there are enough evidence that ROE and ROA influence stock retrun but EVA, DOL, DFL, and DCL do not have any sufficient evidence to influence stock return. Â Keywords: economic value added, operating leverage, financial leverage, combined leverage, return on equity, return on assets, stock return.